Use of Diced Cartilage for Management of Internal Mammary Vessel Exposure Sites in Autologous Breast Reconstruction - Ulf Dornseifer, MD, PhD; My L. Truong; Stephan Grumbrecht, MD; Peter P. Pfeiler, MD; Uli D. Haide, MD, DMD; Philipp Moog, MD, PhD; Michael Kimelman, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Exposure of internal mammary vessels in autologous breast reconstruction often requires removal of a rib cartilage segment, which can lead to breast contour deformity. This study evaluated the use of diced cartilage (DC) to counteract substance loss in the microvascular anastomosis area. Methods:. This retrospective, single-center cohort study included all breast reconstructions in which DC was used from October 2021 to June 2023. Reconstructions using DC were subdivided based on previous breast radiotherapy (DC versus DC with prior breast radiotherapy [DCR]). The control group consisted of an equal number of consecutive reconstructions performed before the use of DC. The effect of DC on breast contour was investigated using magnetic resonance imaging (>6 months postoperative) and photographic documentation (6-month follow-up). Results:. DC was used in 114 of 173 included reconstructions (DC, n = 55; DCR, n = 59; control, n = 59). Magnetic resonance imaging analysis revealed less soft tissue sinking into resection zones in both DC groups (DC 0.2 ± 1.3 mm versus control 6.0 ± 1.6 mm, P = 0.002; DCR 0.4 ± 1.6 mm versus control 6.0 ± 1.6 mm, P < 0.003). Previous irradiation did not affect DC stability. The photographs indicated that there were no deformities after DC use, but deformities occurred in 13.6% of patients in the control group (P < 0.05). Flap failure did not occur in any group. Conclusions:. DC is a safe procedure that prevents contour deformities associated with rib cartilage removal in breast reconstruction, regardless of prior breast irradiation.